DAMPAK PERTUMBUHAN EKONOMI, PROFITABILITAS, RISIKO KREDIT, DAN MODAL INTELEKTUAL TERHADAP PERTUMBUHAN KREDIT PADA BANK UMUM KBMI 3 DI INDONESIA - Anum Nuryani; Renata Fitriani (UNIVERSITAS DHARMAWANGSA, 2026)
Banking plays a strategic role as a financial intermediary institution, where credit growth serves as a key indicator in assessing the effectiveness of fund distribution and overall economic stability. However, the KBMI 3 bank group demonstrates relatively lower credit growth performance compared to KBMI 4 banks and continues to face issues related to high levels of idle credit, indicating suboptimal intermediation functions in supporting economic activities. This study employs a quantitative approach with a causal method to examine the influence of economic growth, profitability (ROA), credit risk (NPL), and intellectual capital (VAIC) on credit growth in KBMI 3 banks, using secondary data from financial statements for the 2020–2024 period analyzed through panel data regression with EViews software. The analysis includes descriptive statistics, classical assumption tests, model selection (CEM, FEM, REM), and hypothesis testing using t-tests, F-tests, and the coefficient of determination (R²) to evaluate relationships and variable effects.The results indicate that economic growth has a positive and significant effect on credit growth, while profitability and intellectual capital do not show a significant influence. In contrast, credit risk has a negative and significant effect, but collectively all variables significantly influence credit growth.